Theoretical Study of NO Dissociative Adsorption onto 3d Metal Particles M(55) (M = Fe, Co, Ni, and Cu): Relation between the Reactivity and Position of the Metal Element in the Periodic Table - Takagi, Nozomi (ACS Omega, 2021)
[Image: see text] NO dissociative adsorption onto 3d metal particles M(55) (M = Fe, Co, Ni, and Cu) was investigated theoretically using density functional theory computations. A transition state exists at higher energy in the Cu case but at lower energy in the Fe, Co, and Ni cases than the reactant (sum of M(55) and NO), indicating that Cu(55) is not reactive for NO dissociative adsorption because NO desorption occurs more easily than the N–O bond cleavage in this case, but Fe(55), Co(55), and Ni(55) are reactive because NO desorption needs a larger destabilization energy than the N–O bond cleavage. This result agrees with the experimental findings. The energy of transition state E(TS) becomes higher in the order of Fe < Co < Ni ≪ Cu. Exothermicity E(exo) (relative energy to the reactant) decreases in the order of Fe > Co > Ni ≫ Cu. These results indicate that the reactivity for NO dissociative adsorption decreases kinetically and thermodynamically in this order. In addition, the E(TS) and E(exo) values show that 3d metal particles are more reactive than 4d metal particles when a comparison is made in the same group of the periodic table. Charge transfer (CT) from the metal particle to NO increases as the reaction proceeds. The CT quantity to NO at the TS increases in the order of Cu < Ni < Co < Fe, identical to the increasing order of reactivity. The negative charges of the N and O atoms of the product (N and O adsorbed M(55)) increase in the order of Ni < Co < Cu < Fe, identical to the increasing order of E(exo) except for the Cu case; in the Cu case, the discrepancy between the order of E(exo) and those of the N and O negative charges arises from the presence of valence 4s electron of Cu because it suppresses the CT from N and O to Cu(55). From these results, one can infer that the d-valence band-top energy of M(55) plays an important role in determining the reactivity for NO dissociative adsorption. Truly, the d valence orbital energy decreases in the order of Fe > Co > Ni ≫ Cu and the 3d metal > 4d metal in the same group of the periodic table, which reflects the dependence of reactivity on the metal element position in the periodic table.